Dual Detection of Hemagglutinin Proteins of H5N1 and H1N1 Influenza Viruses Based on FRET Combined With DNase I - Wang, Zhiyun; Zhao, Qiuzi; Huang, Mengqian; Duan, Yuqin; Li, Feifei; Wang, Tao (Frontiers in Microbiology, 2022)
Influenza A viruses (IAV) are classified based on their surface proteins hemagglutinin (HA) and neuraminidase (NA). Both pandemic H1N1 (pH1N1) and highly pathogenic avian influenza (HPAI) H5N1 viruses pose a significant threat to public health. Effective methods to simultaneously distinguish H1N1 and H5N1 are thus of great clinical value. In this study, a protocol for detection of HA proteins of both H1N1 and H5N1 was established. Specifically, we designed an aptasensor for HA using fluorescence resonance energy transfer (FRET) strategy combined with DNase I-assisted cyclic enzymatic signal amplification. HA aptamers of H1N1 and H5N1 IAVs labeled with various fluorescent dyes were used as probes. Graphene oxide (GO) acted as a FRET acceptor for quenching the fluorescence signal and protected aptamers from DNase I cleavage. The fluorescence signal was recovered owing to aptamer release from GO with HA protein. DNase I-digested free aptamers and HA proteins were able to further interact with more fluorescent aptamer probes, resulting in increased signal amplification. The limits of detection (LOD) of H5N1 HA and H1N1 HA were 0.73 and 0.43 ng/ml, respectively, which were 19 and 27 times higher than LOD values obtained with the DNase I-free system. The recovery rate of HA protein in human serum samples ranged from 88.23 to 117.86%, supporting the accuracy and stability of this method in a complex detection environment. Our rapid, sensitive, and cost-effective novel approach could be expanded to other subtypes of IAVs other than H1N1 and H5N1.